Systematic Analysis Of Studying Sports Tourism (Journal of Pedagogical Inventions and Practices, 2024)
This article describes the multifaceted domain of sports tourism, examining its various dimensions, impacts, and evolving trends. It synthesizes existing literature from diverse disciplines such as tourism studies, sports management, economics, and sociology to provide a comprehensive overview of the subject. Through a systematic analysis of empirical studies, theoretical frameworks, and industry reports, the authors elucidate the complex interplay between sports and tourism sectors. Furthermore, the research scrutinizes the economic ramifications of sports tourism, highlighting its potential to stimulate local economies through increased visitor expenditure, job creation, and infrastructure development. Conversely, it acknowledges challenges associated with hosting sporting events, such as cost overruns, infrastructure strain, and environmental impacts.